2012
DOI: 10.3945/ajcn.111.023499
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support in chronic obstructive pulmonary disease: a systematic review and meta-analysis

Abstract: This systematic review and meta-analysis showed that nutritional support, mainly in the form of ONS, improves total intake, anthropometric measures, and grip strength in COPD. These results contrast with the results of previous analyses that were based on only cross-sectional measures at the end of intervention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
115
3
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 58 publications
(140 reference statements)
5
115
3
9
Order By: Relevance
“…29 The reduction in body weight and FFM in COPD patients is mainly ascribed to a disturbed energy balance, since it has been shown that these patients may exhibit an increased daily energy expenditure compared with healthy subjects. 30 It is not yet clear whether malnutrition in people with COPD is the cause of their deterioration or just part of the progress of the disease 31 ; in any case it may be only partially reversed by nutritional supplementation. 32 The results of this study are in line with those of previous reports showing that body weight depletion is related to a decreased exercise performance in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…29 The reduction in body weight and FFM in COPD patients is mainly ascribed to a disturbed energy balance, since it has been shown that these patients may exhibit an increased daily energy expenditure compared with healthy subjects. 30 It is not yet clear whether malnutrition in people with COPD is the cause of their deterioration or just part of the progress of the disease 31 ; in any case it may be only partially reversed by nutritional supplementation. 32 The results of this study are in line with those of previous reports showing that body weight depletion is related to a decreased exercise performance in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…COLLINS and co-workers [92,93] also published recent meta-analyses using different methods. They did not include all of the same papers, but their findings were broadly in line with the Cochrane review.…”
Section: Treatment Of Weight Loss In Copdmentioning
confidence: 99%
“…The relationship between obesity, the worsening of comorbidities and the symptom burden is poorly investigated [58]. Recent studies suggest that nutrition therapy may improve the condition of severely underweight patients, particularly in combination with a rehabilitation program [5860]. …”
Section: Malnutritionmentioning
confidence: 99%